Strategies to optimize the practice of dental impression during the Covid-19 pandemic - FIGUEIREDO,Viviane Maria Gonçalves de (2021)
ABSTRACT The Covid-19 is a global health threatening pandemic, so dental surgeons need to look for strategies to perform dental care safely for the patient, the dental professional himself, and the dental team. The goal is to design strategies to optimize dental impression practice during the Covid-19 pandemic. The strategies that optimize dental impression practice during the pandemic are to adopt the digital fingerprint workflow. If necessary, a conventional impression technique that favors the professional’s performance, select the impression material that is easy to decontaminate and affinity for the professional; the plaster leak must be performed still inside the dental office, and then the disinfection of the plaster model must be previously sent to the prosthesis laboratory.